Complete Cytoreductive Surgery vs. Debulking Surgery for pseudomyxoma peritonei of appendiceal origin: A propensity score-matched study based on a single-center experience. Issue 9 (September 2021) - Ma, Ruiqing; Lu, Dongmei; Wang, Bing; Zhai, Xichao; Xia, Ao; An, Lubiao; Shi, Guanjun; Cai, Ying; Lu, Yiyan; Pang, Shaojun; Chen, Feng; Xu, Hongbin
Abstract: Objective: This study aimed to report the prognostic predictors and compare the long-term outcomes of complete cytoreductive surgery (CCRS) vs. debulking surgery (DS) in patients with pseudomyxoma peritonei (PMP) of appendiceal origin. Methods: A retrospective analysis of 1008 consecutive patients with PMP undergoing primary surgery from January 2008 to December 2019 was performed. A propensity score-matched (PSM) analysis (1:1) was performed, and oncologic outcomes were compared between the CCRS and DS groups. Results: Out of 1008 patients, 258 patients were excluded. Baseline characteristics differed significantly between the CCRS and DS groups (total n = 750). After PSM, 106 patients were selected from each group and the baseline characteristics were matched between groups. There were significant differences between groups in operative time, the incidence of major complications (P = 0.017), and the numbers of organs removed. The median follow-up was 28 (1–131) months. Median overall survival (OS) for the 212 patients was 52.0 months (95% CI 40.2–63.8), and 10-year OS was 39.0%. Median OS could not be calculated for the CCRS group; in the DS group, this value was 41 months (P = 0.010). The 10-year OS rate was 54.2% in the CCRS group and 31.2% in the DS group. Multivariate analyses identified CCRS ( P  = 0.012) and histopathologic subtype ( P  < 0.001) as independent prognostic factors for OS. Conclusions: In this matched-pair analysis of patients with appendiceal PMP, CCRS was safe and associated with better prognosis than DS. The completeness of cytoreduction and histopathologic subtype were two independent prognostic factors for OS.